THE ROLE OF MOBILE APPLICATIONS IN ENHANCHING POSTPARTUM MOTHER’S KNOWLEDGE ABOUT POSTNATAL CARE: A SCOPING REVIEW - Sari, Fitriana Yuni Permana; Probowati, Rovica; Carvalho, Paulina Fonseca de; Reis, Viana Remiciadas Dores dos (LPPM Universitas Duta Bangsa Surakarta, 2025)
The high rate of postpartum maternal mortality due to health complications is a serious problem that requires innovative solutions. This research aims to explore the role of mobile applications in increasing the knowledge of postpartum mothers and identify the characteristics of effective educational applications. The method used was a Scoping Review with a population of postpartum mothers, using primary research articles in Indonesian and English from 2015-2025 in the Google Scholar and PubMed databases. Results show that apps such as Aponjon, BIDANKU, and Breast Milk Mother significantly improve mothers' knowledge, practices, and self-efficacy through voice messages, texts, and content tailored to the postpartum stage. Characteristics of effective apps include regular communication, personalization of content, focus on maternal and neonatal care, and high interactivity. In conclusion, mobile applications are a potential educational medium to significantly increase the knowledge of postpartum mothers and must be part of the national maternal health strategy to reduce maternal mortality.